Systematic Review of School-Based Programs to Reduce Bullying and Victimization, 1983-2009 - Farrington, David P. ([Verlag nicht ermittelbar], 2014)
The purpose of this systematic review was to assess the effectiveness of school-based anti-bullying programs in reducing school bullying. The following criteria were used for the inclusion of studies in the systematic review: the study described an evaluation of a program designed specifically to reduce school (kindergarten to high school) bullying; bullying was defined as including: physical, verbal, or psychological attack or intimidation that is intended to cause fear, distress, or harm to the victim; and an imbalance of power, with the more powerful child (or children) oppressing less powerful ones; bullying (specifically) was measured using self-report questionnaires, peer ratings, teacher ratings, or observational data; the effectiveness of the program was measured by comparing students who received it (the experimental condition) with a comparison group of students who did not receive it (the control condition). There must have been some control of extraneous variables in the evaluation by (1) randomization, or (2) pre-test measures of bulling, or (3) choosing some kind of comparable control condition; published and unpublished reports of research conducted in developed countries between 1983 and 2009 were included; and it was possible to measure the effect size. Several search strategies were used to identify 89 anti-bully studies meeting the criteria for inclusion in this review: researchers searched for the names of established researchers in the area of bullying prevention; researchers conducted a keyword search of 18 electronic databases; researchers conducted a manual search of 35 journals, either online or in print, from 1983 until the end of May 2009; and researchers sought information from key researchers on bullying and from international colleagues in the Campbell Collaboration. Studies included in the review were coded for the following key features: research design, sample size, publication date, location of the study, average age of the children, and the duration and intensity of the anti-bullying program for both the children and the teachers.